Faktor Determinan yang Mempengaruhi Penerapan Universal Precaution terhadap Pencegahan Risiko HAIs - Nurul Pujiastuti; Angger Rangga Santika; Lucia Retnowati (Jurnal Kesehatan Manarang, 2022)
Infections acquired by patients while hospitalized for at least 72 hours are called Health Care Associated Infections (HAIs). The purpose of the study was to determine the determinant factors that affect the application of universal precaution to the prevention of infection risk in health services by nurses in the room. The research design used was correlation analytic with the type of case control design and the research technique used total sampling technique. The sample size in this study was 36 respondents. The results of Spearman's statistical test, internal factors namely knowledge, training followed, and length of work obtained p value = 0.003 meaning that there was an influence of internal factors (knowledge, training followed, and length of work) on the application of universal precaution. While external factors, namely facilities and colleagues, the value of p = 0.000 means that there was an influence of external factors (facilities and colleagues) on the application of universal precaution. The determinant factors that affect universal precaution are external factors. It is hoped that hospital managers can fulfill the facilities needed by health workers in implementing universal precautions so that the incidence of nosocomial infections can be suppressed.